Solution epitaxy of single-crystal and single-domain KNbO3 film with a great photovoltaic current. (June 2022) - Yang, Q.; Zhang, Z.; Liao, S.; Zhu, R.; Fu, G.; Lin, C.; Chen, J.; Tian, H.; Han, G.; Ren, Z.
Abstract: As a classic ferroelectric material, orthorhombic perovskite KNbO3 demonstrates a large electro-optical coefficient, high refractive index, and excellent nonlinear optical property. These make single-crystal KNbO3 films being long-pursued for lead-free sensor or optoelectronic device applications. However, it remains a challenge to obtain high-quality single-crystal KNbO3 films because of the volatility of potassium at a high growth temperature. In this work, single-crystal KNbO3 films with a tunable thickness have been successfully fabricated by a low-temperature (∼220 °C) hydrothermal epitaxy on cubic single-crystal Nb:SrTiO3 substrates. Interestingly, the KNbO3 film was investigated to adopt a single-domain structure with a polarization direction pointing to the substrate. In-depth characterization reveals an intriguing disordered region of approximately 0.6–1.2 nm because of partial Nb substitution of Ti near the interface, giving rise to the coexistence of Ti 3+ and Ti 4+ ions. Such region is proposed to release a large interface strain energy from a large lattice misfit (∼2.3%) between {011}KNbO3 and {100}Nb:SrTiO3 and reduce interfacial electrostatic energy via screening of the positive polar surface of KNbO3 . This allows to drive a hydrothermal epitaxy of single-crystal and single-domain KNbO3 without forming a typical dislocation. The films demonstrate a great photovoltaic short-circuit current of 15.65 μA/cm 2 under the 375 nm laser irradiation of 500 mW/cm 2 light intensity, and the corresponding photoresponsivity is the highest among the emerged KNbO3 -based materials. Such improvement in the photoresponsivity has been attributed to a successful low-temperature solution epitaxy of single-crystal and single-domain KNbO3 films, where K deficiency can be significantly suppressed. These findings suggest that a solution epitaxy strategy is effective in producing high-quality ferroelectric films for lead-free optoelectronic or self-powered photodetector device applications.